Legal Protection of Coastal Wetlands: A Case Study of Mediterranean Sea - ALSAMARA , Tareck; GHAZI , Farouk (Journal of Ecohumanism, 2024)
The article discusses the legal protections of coastal wetlands by examining a case study of Mediterranean wetlands. It highlights the importance of coastal wetlands within international law and examines the challenges and values of coastal wetlands in the region. Also considered are national policies to protect wetlands through laws and legal strategies. This is part of a larger effort to assess the legal protection of coastal wetlands around the Mediterranean Sea and to assess the Mediterranean environmental legal system. The article concludes that international law protects wetland areas by several conventions at the regional level.